(untitled) (International journal of artificial intelligence, 2025)
This article provides general information on the methods for calculating the seismic impact in assessing the stability of slopes and covers the main methods used in this area. Methods for calculating the seismic impact in assessing the stability of slopes are of great importance in modern construction and geotechnical engineering. These methods are used to determine the movement of the soil during an earthquake and its effect on structures, as well as to ensure the safety and strength of structures. The development and improvement of methods for calculating the seismic impact will increase the safety of construction projects and create the possibility of implementing them in complex natural conditions. This article discusses the methods for calculating the seismic impact used in assessing the stability of slopes and their practical significance. The results of the study are presented based on the H/V method, i.e. the Response spectrum.